Sharps Safety and Management among Dental Practitioners - Shuchi Tripathi; Raghuwar Dayal Singh; Rameshwari Singhal; Richa Khanna; Deeksha Arya; Swapnil Parlani (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Background: The potential for transmission of blood borne infections is highest during handling of  needles and sharps. The factors which relate commonly to sharps injuries include the inadequate design or inappropriate placement of sharps disposal container, overfilling of sharps disposal container and inappropriate sharps disposal practices by the care provider during patient treatment. The present study was undertaken to assess the knowledge and practice of sharps use and disposal in dentists practising in government and private sectors and also to provide correct methods and procedure regarding sharp use and disposal to increase awareness. Methods: A questionnaire comprising of 20 self-administered questions regarding knowledge, use and disposal methods of sharps in dentistry was prepared. The questionnaire was sent to 220 dentists practising in Lucknow and nearby area. Out of them 86 dentists in government teaching institute and hospitals, 45 dentists in private teaching institute and hospitals and 29 dentists of private clinic had answered back. The resulting data was compared and statistically analyzed.  Result: Only 11% dentists were fully aware about the type of sharps used in the dentistry. 79% of dentists prefer to use gloves always at the time of injection. 81% of the dentists were agreed with use of mechanical needle cutter and electrical needle destroyer to destroy the needle tips, however only 37% were actually using these methods. 66% answered that incineration is best method of fi nal disposal of sharps. Conclusion: There is somewhat lack of motivation and awareness regarding the sharps use and their maintenance among dentists, which needs special attention.